2016
DOI: 10.1093/jisesa/iew075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Standard Loose Plastic Packaging for the Management ofRhyzopertha dominica(F.) (Coleoptera: Bostrichidae) andTribolium castaneum(Herbst) (Coleoptera: Tenebriondiae)

Abstract: Three standard foodstuff plastic packaging namely polyethylene (PE), polypropylene (PP), and polyvinylchloride (PVC) were evaluated for management of lesser grain borer Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) and red flour beetle Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). Resistance parameters in packaging were recorded as punctures, holes, penetrations, sealing defects, and invasions with two thicknesses and tested for two lengths of time. Damages like punctures, holes and penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
4
10
0
1
Order By: Relevance
“…T. castaneum beetles could only manage to damage and create holes in polyethylene packets and subsequently it entered through holes in polyethylene packed wheat flour. This study is in agreement with our previous findings in which it was proved that out of three different packaging materials tested; polyethylene was a susceptible packaging material against red flour beetle in 2013, 2014and 2016(Qasim et al, 2013Hassan et al, 2014;Hassan et al, 2016). This study is also in agreement with a study which reports that polymers like polyethylene and cellophane could be penetrated by certain stored grain insect pests (Cline, 1978;Allahvaisi, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…T. castaneum beetles could only manage to damage and create holes in polyethylene packets and subsequently it entered through holes in polyethylene packed wheat flour. This study is in agreement with our previous findings in which it was proved that out of three different packaging materials tested; polyethylene was a susceptible packaging material against red flour beetle in 2013, 2014and 2016(Qasim et al, 2013Hassan et al, 2014;Hassan et al, 2016). This study is also in agreement with a study which reports that polymers like polyethylene and cellophane could be penetrated by certain stored grain insect pests (Cline, 1978;Allahvaisi, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…We have so far studied behaviour of three types of loose plastic packaging in terms their susceptibility to penetration or invasion by T. castaneum or other storage pests and fumigation efficacy by phosphine as affected by different packaging has been elucidated (Qasim et al, 2013;Hassan et al, 2014;Hassan et al, 2016). This research is for the first time about investigation of resistant packaging against T. castaneum for a period of three months.…”
Section: Introductionmentioning
confidence: 99%
“…compared to thick packaging, and that polypropylene and polystyrene packaging were completely penetrated when used at thinner thicknesses. Our results are in agreement with our recent findings showing that damage was more pronounced in thin packaging than in thicker packaging (Hassan et al 2016), and our more recent studies showed that transparent polyethylene packaging became particularly susceptible for packed foodstuff against Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) when used at 0.02 mm thickness followed by polypropylene at 0.02 mm; no damage occurred in polyvinylchloride packaging at 0.03 mm thickness (Yar et al 2017). Our results also are consistent with the findings of Shukla et al (1993), who reported that khapra beetles can penetrate packaging of less than 0.08 mm thickness.…”
Section: Discussionsupporting
confidence: 94%
“…These results show that transparent polyethylene packaging is superior to the polyvinylchloride packaging. These results are in agreement with our previous findings that showed mortality of pest species was lower in polyvinylchloride packaging than in transparent polyethylene or polypropylene packaging (Hassan et al 2016;Akram et al 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Recientemente se ha observado que la capacidad para degradar polímeros plásticos por escarabajos va más allá del género Tenebrio. Los adultos del escarabajo Tribolium castaneum han mostrado la capacidad para producir daños estructurales en recipientes de PE(Hassan, Qasim, Iqbal & Jamil, 2014;Hassan et al, 2016) y en bloques de EPS, donde se pudo después de 16 días de tratamiento, tiempo durante el cual las larvas pudieron subsistir con una dieta exclusiva de material plástico. El análisis del humus generado durante el tratamiento sugiere que existe una despolimerización parcial de las cadenas largas del EPS dentro del tracto intestinal de las larvas con la consecuente formación de productos de bajo peso molecular, confirmándose la biotransformación de este material.…”
unclassified